The triple challenges associated with age‐related comorbidities in Down syndrome. (19th March 2013) - Glasson, E. J.; Dye, D. E.; Bittles, A. H.
Abstract Background Major increases in the survival of people with Down syndrome during the last two generations have resulted in extended periods of adulthood requiring specialist care, which in turn necessitates greater understanding of the nature, timing and impact of comorbidities associated with the disorder. Method The prevalence of five comorbidities reported as common in adults with Down syndrome, visual impairment, hearing impairment, epilepsy, thyroid disorders and dementia was assessed by decade of life. Results From early adulthood, people with Down syndrome are at enhanced risk of developing new comorbidities and they may present with multiple conditions. Three specific challenges are identified and discussed: are comorbidities detected in a timely manner, is the clinical progress of the disorder adequately understood, and who is responsible for the provision of care? Conclusions Further detailed investigations into the development and treatment of comorbidities across the lifespan are needed for a successful longitudinal approach to healthcare in people with Down syndrome. Implementation of this approach will better inform healthcare providers to ensure continuity of care with advancing age.